[OP.1D.07] EARLY SIGNS OF END-ORGAN DAMAGE IN RETINAL ARTERIOLES IN TYPE 2 DIABETIC IN COMPARISON WITH HYPERTENSIVE PATIENTS. (September 2016) - Jumar, A.; Ott, C.; Kistner, I.; Friedrich, S.; Harazny, J.M.; Schmieder, R.E.
Abstract : Objective: Eutrophic and hypertrophic remodeling are major vascular hallmarks for hypertension and diabetes associated microvascular end-organ damage in peripheral arterioles. Retinal microvascular arterioles can nowadays be easily analyzed by non-invasive tools. The aim of this study is to compare retinal arterioles of diabetic with those of hypertensive patients and healthy individuals to identify diabetes specific early signs of microvascular end-organ damage. Design and method: Retinal parameters were assessed in 158 hypertensive (mean age 52 years), 107 patients with non-insulin-dependent type-2 diabetes mellitus (T2DM) (mean age 61 years, median disease duration 60 months) and 86 healthy individuals. Wall thickness (WT), wall-to-lumen-ratio (WLR) and cross-sectional area (CA) of retinal arterioles (80–140 μm) were measured non-invasively and in vivo by scanning-laser-Doppler-flowmetry (Heidelberg Engineering, Germany). Results: Patients with T2DM showed no significant difference in WT (14.2 ± 3 vs. 13.3 ± 4, p = 0.151), WLR (0.375 ± 0.086 vs 0.347 ± 0.094, p = 0.664) and CA (4192 ± 1093 vs 3862 ± 1546, p = 0.108) in comparison with hypertensive patients, but compared to the healthy control group greater WT (13.3 ± 4 vs 12.9 ± 3.1, p = 0.011) and WLR (0.347 ± 0.094 vs 0.314 ± 0.078, p = 0.001). In the diabetic group there was a correlation between both WT (r = 0.196, p = 0.050) and CA with diabetes duration (r = 0.204, p = 0.040). Consistently the subgroup of patients with diabetes duration of more than 60 month showed greater WT (14.9 ± 4, p < 0.001) and CA (4526 ± 1127, p = 0.003) compared to the hypertensive group. Conclusions: In the early stage of T2DM the hypertrophic remodeling described in subcutaneous arterioles was not seen in the retinal arterioles. However, hypertrophic remodeling in retinal arterioles was found in diabetic patients with more than 60 month duration of disease.